# math

posted by .

if cotx+tanx=a and secx-cosx=b then prove that (a^2b)^0.6667 -(ab^2)^0.6667=1

• math -

a^2b^(2/3) - (ab^2)^(2/3)
(a^2b)^(1/3) - (ab^2)^(1/3)(a^2b)^(1/3) + (ab^2)^(1/3)

ignoring the x's for a bit,

a^2 = (cot+tan)^2 = cot^2 + 2 + tan^2 = csc^2 + sec^2
a^2b = sec^3

b^2 = (sec-cos)^2 = sec^2 - 2 + cos^2
ab^2 = tan^3

(a2b)^(2/3) = sec^2
(ab^2)^(2/3) = tan^2

sec^2 - tan^2 = 1

## Similar Questions

1. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
2. ### Simplifying with Trigonometry Identities

Hi, I am a senior in High School having a really difficult time with two problems. I have to prove using the trigonometric identities that they equal each other but I am having a really hard time trying to get them to equal each other. …
3. ### drwls

My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
4. ### trig

prove cosx+cotx/secx+tanx =cosxcotx
5. ### college algebra

I think this is an exponential equation. I can not figure out how to put the equation into the TI-84 to get the approximate form 3/5 ln(5x-1)+1 =1.4 subtract 1 from sides and divide by 3/5 lh(5x-1)=0.6667 Put in logarithm form e^0.6667=5x-1 …
6. ### precal

1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a negatvie:( …
7. ### Math

Im really struggling with these proving identities problems can somebody please show me how to do these?
8. ### Math

Im really struggling with these proving identities problems can somebody please show me how to do these?
9. ### Precalculus/Trig

I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …
10. ### Pre-calculus

Prove the following identities. 1. 1+cosx/1-cosx = secx + 1/secx -1 2. (tanx + cotx)^2=sec^2x csc^2x 3. cos(x+y) cos(x-y)= cos^2x - sin^2y

More Similar Questions